PRODUCT INNOVATION AND UTILIZATION OF DIGITAL MARKETING FOR BUSINESS SUSTAINABILITY DURING A PANDEMIC IN CULINARY BUSINESS - Yande Ryan Ambaramika Adnyana; I Gusti Ngurah Putra Suryanata (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
The culinary business is growing every day because it is a very profitable business, but running a culinary business when the pandemic by COVID-19 is very difficult, even some business sectors are almost paralyzed, which ultimately affects the country's economy and causes a slowdown in global economic activity. This study aims to find action in the culinary business to maintaining business continuity during the pandemic. To survive the current situation, the owner of the roof sekarjambu must be brave in building a business, and product innovation include planning the marketing system, packaging, and brand. What will it be like, especially in today's digital world, making everything easier to market business products. The research is a qualitative method with primary data sources from interviews, observations and documentation, and secondary data sources. To achieve clear and focused research results, the authors choose informants who know, master the problem and are directly involved, including business owners, employees and consumers. The Roof Sekarjambu applies innovation and digital marketing to maintain the sustainability of the culinary industry during the current COVID-19 pandemic crisis, which has weakened the purchasing power of consumers and the economy in all sectors. One of them is in the culinary field